The Transition from Green to Blue IT and How Organisations Can Achieve Net Zero Goals - Purohit, Vijay (Digital Repository of Theses, 2026)
As the world races toward net-zero goals, the role of IT is evolving from just being a support function to becoming a key player in sustainability. This research looks at how organizations can move from Green IT which focuses mainly on reducing energy use and waste to a more ambitious model called Blue IT. Blue IT isn’t just about being eco- friendly; it’s about embedding sustainability into every part of IT operation, from strategy and design to procurement and disposal. The study takes a practical approach by combining interviews with IT leaders, government policymakers, and experts from Global Competency Centers with survey responses from professionals across industries. It explores what’s working, what’s not, and what’s missing when it comes to making IT truly sustainable. It also digs into how new technologies like AI, IoT, and blockchain can help optimize resources and support sustainability goals. Through real-world case studies, the research highlights common challenges like budget constraints, inconsistent global policies, and lack of awareness especially in smaller organizations. It also emphasizes the importance of government policies, cross-functional teamwork, and building a culture that encourages “green thinking” across all levels. One of the key takeaways is the need for better tools to measure and report on IT’s environmental impact, including emissions, energy use, and even the carbon footprint of supply chains. The research aims to provide a clear, flexible roadmap that organizations can actually use not just another theoretical model that sits on a shelf. In the end, this work hopes to help IT leaders and decision-makers make sense of where they are today and what steps they can take next to align their digital strategies with long- term sustainability goals. It’s about turning good intentions into action and helping IT become a real force for climate progress.